Scenarios for use of biogas for heavy-duty vehicles in Denmark and related GHG emission impacts - Jensen, Steen Solvang; Winther, Morten; Jørgensen, Uffe; Møller, Henrik B. (Proceedings from the Annual Transport Conference at Aalborg University, 2017)
Biogas may be a promising alternative fuel, mainly for heavy-duty vehicles, that can reduce CO2 emissions via substitution of fossil fuels and further reduce methane emissions from agricultural manure handling. However, as methane is a potent climate gas loss of methane from production to use of biogas is of concern. This study has analysed the potential biomass and biogas production from all Danish organic waste sources under different scenario assumptions for future scenario years. The analysis includes energy demand of the road transportation sector by means of transport and fuel types, and potential use of the limited biogas resource taking into account alternative fuel options available for transportation (electricity, hydrogen, biofuels). Further, the total differences in fuel consumption and GHG emissions due to the replacement of diesel-powered heavy-duty vehicles by gas-powered heavy-duty vehicles are estimated in a well-to-wheel perspective taking into account methane losses.